Factors Related to Injury Prevention Programming by Missouri School Nurses. (August 2018) - Rebmann, Terri; Weaver, Nancy L.; Elliott, Michael B.; DeClue, Rich W.; Patel, Niral J.; Schulte, Lauren
Schools often offer injury prevention (IP) programs, but little is known about the types of programs provided or how school nurses decide which to choose. Nurses in the Missouri School Health Services Staffing Survey Database were sent a survey in spring, 2011, to describe school-based IP efforts being offered. A multivariate linear regression was conducted to delineate factors associated with offering IP programs. In total, 522 school nurses participated (33% response rate). The highest priority for selecting an IP program was perceived program effectiveness (92.3% agreement, n = 482). Determinants of offering IP programs included being asked to identify a speaker, being a high school, receiving funding in the last year, prioritizing evidence-based programs, perceiving that administrators support professional development, and knowing how to address patterns of injuries. School nurses should be competent in planning, implementing, and evaluating IP programs, and additional training may be required to accomplish this.